2016
DOI: 10.11648/j.ijmea.20160406.15
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the Hertz Contact Theory to Rolling Rubber Cylinders Model

Abstract: Hertz contact theory (HCT) is a study of contact stress and deformation which is widely used in many engineering fields. However, there are many limiting conditions for the applications of the HCT, in this paper, the contact model between a plastic cylinder and a rubber cylinder does not fit two limiting conditions: Small deformation and no rigid body motion. By applying three-dimensional finite element models, the deformation and the maximum contact stress of two rotating cylinders have been analyzed. Compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Therefore, the results are more reliable at high velocities when the rubber has higher stiffness. Hongyan et al [36] also studied the applicability of the Hertz contact theory to large deformation using finite element methods. They found that the Hertz contact theory can predict the maximum contact stress under large deformation with about 2% error and overestimates the contact length with about 33%, but they did not validate the results with experiments.…”
Section: Gw Theory and The Improved Versionmentioning
confidence: 99%
“…Therefore, the results are more reliable at high velocities when the rubber has higher stiffness. Hongyan et al [36] also studied the applicability of the Hertz contact theory to large deformation using finite element methods. They found that the Hertz contact theory can predict the maximum contact stress under large deformation with about 2% error and overestimates the contact length with about 33%, but they did not validate the results with experiments.…”
Section: Gw Theory and The Improved Versionmentioning
confidence: 99%